The first wife - Spindler, Erica, 1957- (St. Martin's Press, 2015)
"As a child, Bailey Browne dreamed of a knight in shining armor swooping in to rescue her and her mother. As she grows older, those dreams transform, becoming ones of a mysterious stranger who will sweep her off her feet and whisk her away from her ordinary existence. Then, suddenly, there he is. Despite the ten year difference in their ages, her working class upbringing and his of privilege, Logan Abbott and Bailey fall deeply in love. Marriage quickly follows. But when Logan brings her home to his horse farm in Louisiana, a magnificent estate on ninety wooded acres, her dreams of happily-ever-after begin to unravel."--